A multiscale 3D hotspot-rich nanostructured substrate for biomolecular detection of SARS-CoV-2 - Sahoo, Smruti R.; Huang, Chun-Ta; Tsai, Kunju; Wang, Gou-Jen; Chang, Cheng-Chung (Applied physics reviews, 2023)
The current fabrication methods of surface-enhanced Raman scattering (SERS) chips used for biological detection mostly require antibodies conjugated on nanostructured metals or additionally connected to a reporter, which leads to complicated fabrication processes and increases the cost of these chips. More importantly, only a single-layer (2D) signal source is generated on the substrate of the chip, resulting in poor sensitivity. Herein, we constructed a single-component, multiscale, three-dimensional SERS (M3D-SERS) substrate from silver nanowires (AgNWs) packing. According to our results, the Raman enhancement effect of the M3D-SERS substrate was related to the degree of AgNWs stacking along the z axis. In addition, the light source-dependent plasmonic partition and hotspot formation of the M3D-SERS substrate were evaluated by the finite integration technique to prove that M3D-SERS offers advantages, with isotropic localized surface plasmon resonance as well as homogeneous hotspot distribution, for SERS over its 1D and 2D counterparts. Experimentally, the optimal construction of the M3D-SERS chip was explored and established based on the Raman signal enhancement of bovine serum albumin, and consequently, the efficiency of the M3D-SERS chip in detecting SARS-CoV-2-related biomolecules was investigated based on the detection superiority to biomolecules. This study demonstrates a simple, label-free, pre-treatment-free potential biosensor technology that can be used in healthcare units. Furthermore, in combination with a suitable laser light source, this technology can be applied for efficient detection in point-of-care tests with a handheld spectrometer.